Los costes de la política de cambio climático: una aproximación teórica - García Fernández, Cristina (Nómadas. Critical Journal of Social and Juridical Science, 2010)
This paper presents a mathematical model applied to the problem of climate change. We believe in the necessity of applying gradual mitigating policies and we know that the performance of climate change policies and the evolution of certain economic and social variables give way tome some economic cost, that is, the cost of reducing carbon emissions. The effective performance of economic climate change policies –that have the goal of reducing greenhouse gases- and the control of the most influent variables in the expulsion of the emissions cause a minimum cost and a very strict coordination between the different policies so that the evolution from the initial state to the final required would be most efficient. The model optimizes the trajectory these variables should take from the initial point to the final required, minimizing the cost of this change.